Comparison of the Effectiveness of Group Compassion Training and Group Choice Theory Training on Mindfulness and Needs Satisfaction in Couples at Risk of Divorce in Rasht - Solhi Oskouei, Paniz; Azimi, Dariush (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to compare the effectiveness of group compassion training and group choice theory training on mindfulness and needs satisfaction in couples at risk of divorce in Rasht. Methods: This research employed a quasi-experimental design with a pre-test, post-test, and control group, including a follow-up phase. The statistical population consisted of couples at risk of divorce who referred to counseling centers approved by the Welfare Organization of Rasht in 2023. A total of 60 participants were selected through convenience sampling and randomly assigned to two experimental groups (compassion training and choice theory training) and one control group (20 participants in each group). The research utilized the Mindful Attention Awareness Scale (MAAS) and the Basic Psychological Needs Satisfaction Scale as the main instruments. Both interventions were conducted in eight 90-minute sessions. Data were analyzed using repeated measures ANOVA with SPSS 26. Findings: The results revealed significant differences in the effectiveness of group compassion training and group choice theory training (p < .01). Group compassion training was found to be more effective than choice theory training in improving mindfulness and needs satisfaction. Both training types significantly impacted mindfulness and needs satisfaction in couples at risk of divorce (p < .01). Conclusion: Both group compassion training and group choice theory training were effective in improving mindfulness and needs satisfaction among couples at risk of divorce, with compassion training showing greater effectiveness. These findings suggest that compassion training may provide a more suitable approach for enhancing psychological well-being in couples facing marital challenges.